Decentralized power and the municipal grid: high tensions around an urban common good in the Western Cape (South Africa) - (:unkn) unknown (My University, 2021)
In a time of profuse use of the concepts of commons and common good, it is tempting to mobilise them to analyse the evolution of South African municipal electricity networks. After a review of the relationship between these concepts and the electricity network as discussed in the literature, the article distinguishes between the notion of collective good (the infrastructure) and that of common good (the political project of urban integration and its values) of which the network is both the material embodiment and the socio-technical vector in South Africa. It first shows that, at the present stage, the rise of photovoltaic solar energy, resulting from individual initiatives by wealthy urbanites or corporate strategies, cannot be interpreted in terms of electric commons. It then explains why the destabilization of the municipal electricity distribution function under the effect of a still poorly controlled solar revolution threatens the existence of an urban common good backed by the grid since 1994. Finally, it returns to the proposed distinction between a collective good and the common good, showing that it is useful for interpreting the circumstances that made possible the alignment between an inherited material infrastructure and the objectives of the post-apartheid urban project. However, the concepts of commons and common good only imperfectly allow us to understand what is at stake today in the municipal electricity networks. Indeed, the difficulties experienced by Western Cape municipalities in combining all the socio-technical devices and in reinventing forms of regulation that constitute a new redistributive model give rise to fears that solar PV will only be appropriated by city dwellers and companies that have the financial means. This could lead to the emergence of off-grid clubs that would create an electricity divide in highly unequal cities.
Keywords: African Research